1973
DOI: 10.1099/00207713-23-3-238
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus alcalophilus subsp. halodurans subsp. nov.: An Alkaline-Amylase-Producing, Alkalophilic Organism

Abstract: An alkaline-amylase-producing, alkalophilic bacillus, NRRL B-388 1, was characterized and compared with Bacillus sp. ATCC 21591 and Bacillus alcalophilus Vedder strain NCTC 4.553 (=ATCC 27647), which is here designated as the type strain of B. Irlcalophilus. All three strains contained. motile, gram-positive rods with rounded ends and swollen, clavate sporangia with oval, terminal to subterminal endospores. All three strains grew in soybean broth; were facultatively anaerobic; hydrolyzed starch, gelatin, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The percentage of sequences that were affiliated with thermophilic lineages and lineages that contain thermophilic representatives was much higher in drilling mud than in drilling water, which reflects the elevated temperatures associated with mud formulation. Several of the Bacillus-affiliated sequences in drilling mud samples were similar (Ͼ97.0%) to those of Bacillus alcalophilus, which is a known alkaliphile (9). These sequences were observed only in drilling muds, which suggests that the increase in pH associated with mud formulation stimulated alkaliphilic microorganisms.…”
Section: Discussionmentioning
confidence: 71%
“…The percentage of sequences that were affiliated with thermophilic lineages and lineages that contain thermophilic representatives was much higher in drilling mud than in drilling water, which reflects the elevated temperatures associated with mud formulation. Several of the Bacillus-affiliated sequences in drilling mud samples were similar (Ͼ97.0%) to those of Bacillus alcalophilus, which is a known alkaliphile (9). These sequences were observed only in drilling muds, which suggests that the increase in pH associated with mud formulation stimulated alkaliphilic microorganisms.…”
Section: Discussionmentioning
confidence: 71%
“…Soil samples (each 0.1 g) collected around thi~ University and in the vicinities of Asahi (Osaka) and Shimogamo (KyoOffprint requests to: Yuzuru Suzuki to) were added to test tubes (1.8 × 18 cm), each containing 5 ml medium 1 [0.3% (w/v) KH2PO4, 0.2% yeast extract, 1.0% casein, 0.2% peptone, 0.002% MgSO4.7H~O, 0.005% FeSO4-7H20, 0.0002% MnC12-4H20, 0.0001% Na2MoO4.2H~O, 0.002% CaC12.2H20 and 1% Na2CO3 (pH 10.3 after autoclaving; Boyer et al 1973)], and incubated for 48 h at 37 ° C with the tubes leaning at an angle of about 10% After one more enrichment of cultivation on medium I, 120 cultures were obtained by streaking the samples on medium I agar (3%) plates followed by incubation for 18 h at 37 ° C. Cells of each isolate, grown for 18 h at 37 ° C on a medium I agar slant (8 ml/tube), were suspended in 5 ml of 0.85% NaC1, inoculated to an absorbance at 660 nm (A660) of 0.02--0.03 in a test tube containing 5 ml medium I, and shaken at 37 ° C for 8 h at 110 oscillations/min (6.5-cm amplitude) on a reciprocal shaker. The culture was centrifuged (6°C, 30 min, 80009) , and the supernarant was assayed for protease.…”
Section: Methodsmentioning
confidence: 99%
“…Strain KP 1239, which grew at 24°-53 ° C and best at 45°C on medium II [0.3% KHzPO4, 0.5% NaHCO3, 0.5% peptone and 0.5% yeast extract (pH 8.3)], was assigned to a strain of B. alcalophilus subsp, halodurans (Boyer et al 1973;Claus and Berkeley 1986). The motile, amylolytic, proteolytic, rod-shaped vegetative cells (0.9-1.2 × 10-15 ~tm) were positive to Gram, catalase, and oxidase reactions, and produced terminally swollen sporangia with oval spores (0.9-1.2 × 1.2-1.3 lxm) after 18 h growth at 37°C on medium I1.…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme can hydrolyze 70% of starch to yield glucose, maltose, and maltotriose and the enzyme is a type of saccharifying α-amylase. Subsequently, considerable diversity of α-amylases has been reported: Boyer et al 35) reported an alkaline amylase in the strain NRRL B-3881, which was the second report of an alkaline amylase. The B-3881 amylase had its optimum pH for enzyme action at 9.2.…”
Section: )mentioning
confidence: 99%